PROBLEM-BASED LEARNING APPLICATION ON ENGLISH ESSAY WRITING CLASS - David Berthoni Manalu; Rudiarman Purba (PT. Migas Centre Sidjabat, 2024)
This research was designed to find the effect of implementing problem-based learning on students' ability to write essays. This research is an experiment which uses quantitative analysis to process the data. The subjects studied were students in the 5th semester of 5 2022/2023, FKIP, HKBP Nommensen University, Pematangsiantar. The samples used were 40 students each for the experimental class and control class. The instrument used in this research was an essay test. The research results prove that problem-based learning can improve students' ability to write essays. This can be seen from the results of the t test (9.38) which is greater than the t table (2.68) at the significance level of 0.05. By implementing problem-based learning, students are greatly helped in expressing organized ideas in writing.